SCIENTIFIC-METHODICAL APPROACH TO PROCESSES INVOLVING "FUNDAMENTAL", "STRANGE" AND "CHARMING" PARTICLES DURING PRACTICAL TRAINING - Madaliyev Akmaljon Makhammadjonovich (Galaxy International Interdisciplinary Research Journal, 2022)
In practical classes, analyzing and solving issues related to particles belonging to the class of hadrons with in-depth study of processes with the participation of a fundamental, strange and fascinating particle contributes a lot to the effectiveness of mastering elementary particle physics. In the process of practical training, it is considered important to dwell on what the universe that surrounds us is made of in order to describe particles belonging to the class of fundamental, strange and fascinating particles. As we know, the basis of any substance is atoms. Atoms combine to form molecules, and they, in turn, combine to form substances.